Self-esteem, school performance, and self-efficacy in risky-situation of child-waste pickers in Mandurriao, Iloilo City - Gonzales, Rommel V.; Valenzuela, Maria Juvy A.
This study sought to find the sels-esteem, school performance, and self-efficacy in risky-situation of child-waste pickers in Mandurriao City Dumpsite. Seventy-four (74) child-waste pickers between the ages of 9-20 years old were purposively chosen to serve as respondents., Two instruments were utilized for this study namely: Rosenberg Self-esteem scale (1965) and Self-efficacy in risky-situation scale developed by the researchers. Results showed that the child-waste pickers in Mandurriao Iloilo City Dumpsite are low performers in school. They have high levels of self-esteem indicating that they are globally satisfied with themselves. Likewise, they are average self-efficacious risk takers however, this does not seem to be related to their positive evaluation toward themselves.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Child-waste pickers -- Self-esteem.; Child-waste pickers -- Mandurriao, Iloilo City; Child-waste pickers -- School performance; Child-waste pickers -- Self-efficacy.